A clinical study of postpartum depression and its association with postnatal factors - Mathur, Poonam; Mathur, Rahul; Singh, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The postpartum period is a time of tremendous emotional and physical change for most women as they adapt to new roles and alteration in their physiology. Postpartum depression has seen its rise lately. Multiple factors might be responsible for causation. Symptoms include depression, tearfulness, emotional liability, guilt, anorexia, sleep disorders, feeling inadequate, detachment from the baby, poor concentration, forgetfulness, fatigue, and irritability. Methods: We have conducted a study in 225 postpartum females and assessed them for depression and associated postnatal depression. The 10-question Edinburgh Postnatal Depression Scale (EPDS) was used for assessing depression. Results: Depression was evaluated as 6%. It was also found that 2% mothers with IUD babies developed postnatal depression. 1.33% cases with babies having congenital anomaly developed postnatal depression. 1.33% cases with babies having nursery admission developed postnatal depression. This has been correlated with many other studies. Conclusions: It is found that perinatal factors do affect postnatal depression as it is found in mothers who have an adverse perinatal outcome. Further research is implicated in this field.